Penundaan Pemilihan Kepala Desa Serentak Tahun 2023 di Kabupaten Labuhanbatu Selatan - Rizki Wahyuni; Mirza Nasution; Eka Nam Sihombing (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The enactment of Law No. 6 Year 2024 on Villages in Indonesia has made the Village Head Election System in Indonesia better and more organized. Village Head Election is a form of democratic party at the village level that is conducted simultaneously in all districts/cities. The policy for the implementation of simultaneous Village Head Elections as intended is determined by the regency / city government by regency / city regulation. The method used is a qualitative method, research that produces descriptive data analysis, namely analysis that describes the state or status of the phenomenon with words or sentences, then separated according to its category to obtain conclusions from all the problems studied by collecting data, qualifying then connecting theories related to the problem and drawing conclusions to determine the results Data obtained from field research and literature studies are collected and then analyzed. The postponement of the 2023 Simultaneous Village Head Election in Labuhanbatu Selatan Regency occurred due to several factors including the Budget Factor from the Regional Budget and the Politicization Factor of a Regent so that legal uncertainty was the impact of the postponement of this village head election. Keyword: Delay, Village Head Election, Labuhanbatu Selata Regency